Pembuatan Sistem Penjualan Spare Part Mobil Berbasis Web Pada Usaha “Asen” - Setiawan, Steven; Dewayani, Ery (Jurnal Sistem Informasi Galuh, 2024)
The rapid development of technology nowadays and fairly easy access have resulted in increased use of technology by society. The use of technology can make it easier for people to search for information, both locally and internationally. Technological developments also have an influence in the business sector, where their use can help businesses increase the number of potential buyers who look at the business and the profits of the business. The "Asen" business is a car spare parts business founded by a freelancer named Tomy Setiawan Tjua who has been involved in the world of car spare parts for 20 years. The sales system in this business still uses a manual method where prospective buyers are required to contact the business owner first to carry out transactions. Creating a website-based sales system for the "Asen" business is to make it easier for business owners to sell car spare parts and make it easier for buyers to purchase car spare parts. Creating this website-based sales system uses Laravel as a PHP-based website platform, then MySQL as a data storage place, and Visual Studio Code application as a place to write system code.